On the Dirichlet problem for generalized Cauchy-Riemann equations - Gutlyanskii, V.Yu.; Ryazanov, V.I.; Salimov, A.R.; Salimov, R.R. (Доповіді НАН України, 2025)
Here we give a survey of consequences of the theory of the Beltrami equations from the complex analysis for the Dirichlet problem to generalized Cauchy-Riemann equations ▽v = B▽u in the real plane R² that describe flows of fluids in anisotropic and inhomogeneous media, where B is a 2 × 2 matrix valued coefficient and the gradients ▽u and ▽v are interpreted as vector columns. Moreover, we clarify the relationships of the latter to the A-harmonic equation div (A▽u) = 0 with matrix valued coefficients A that is one of the main equations of the potential theory, namely, of the hydromechanics (fluid mechanics) in anisotropic and inhomogeneous media in the plane. The survey includes a series of effective integral criteria for existence of regular solutions of the Dirichlet problem with continuous data in arbitrary bounded simple connected domains to generalized Cauchy-Riemann equations with matrix coefficients in the case of anisotropic and inhomogeneous media. Стаття містить огляд наслідків теорії рівнянь Бельтрамі з комплексного аналізу для задачі Діріхле до узагальненого рівняння Коші—Рімана ▽v = B▽u на дійсній площині R², що описує потоки рідини в анізотропних та неоднорідних середовищах, де коефіцієнт B представлено у вигляді 2 × 2 матриці, а градієнти ▽u та ▽v інтерпретуються як вектор-стовпці. Крім того, з’ясовується зв’язок цього рівняння з A-гармонічним рівнянням div(A▽u) = 0 з матричними коефіцієнтами A, яке є одним із головних рівнянь теорії потенціалу, а саме гідромеханіки (механіки рідин) в анізотропних та неоднорідних середовищах на площині. Огляд включає низку ефективних інтегральних критеріїв існування регулярних розв’язків задачі Діріхле з неперервними даними в довільних обмежених однозв’язних областях для узагальнених рівнянь Коші—Рімана з матричними коефіцієнтами в умовах анізотропних та неоднорідних середовищ.